2002
DOI: 10.1016/s0002-9440(10)64457-4
|View full text |Cite
|
Sign up to set email alerts
|

Aging Accelerates Endotoxin-Induced Thrombosis

Abstract: Although older subjects are susceptible to thrombosis under septic conditions, the underlying molecular mechanisms have not been fully elucidated. Since elevated plasminogen activator inhibitor-1 (PAI-1) primarily contributes to endotoxin-induced thrombosis, we first compared the induction of PAI-1 by lipopolysaccharide (LPS) between young and aged mice. The higher induction of PAI-1 antigen and mRNA with increased renal glomerular fibrin deposition was observed in LPS-treated aged mice compared to young mice.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(22 citation statements)
references
References 34 publications
(37 reference statements)
1
20
1
Order By: Relevance
“…LPS is known to activate the vascular endothelium and promote the formation of spontaneous thrombi 3134 . To study the effects of inflammation-induced coagulation, we exposed p16 INK4a transgenic and wild-type mice to low dose LPS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…LPS is known to activate the vascular endothelium and promote the formation of spontaneous thrombi 3134 . To study the effects of inflammation-induced coagulation, we exposed p16 INK4a transgenic and wild-type mice to low dose LPS.…”
Section: Resultsmentioning
confidence: 99%
“…These markers are commonly used to measure activation of coagulation (TAT) 47,48 and endothelial activation (PAI-1) 49,50 . Yamamoto et al showed that aged mice had elevated induction of PAI-1 compared to young mice after LPS treatment, suggesting PAI-1 is important in endotoxin-induced thrombosis 31 . Since PAI-1 is both a marker of endothelial cell senescence and a potent fibrinolysis inhibitor, 51 it could also participate in the delayed thrombus resolution seen in p16 INK4a transgenic mice.…”
Section: Discussionmentioning
confidence: 99%
“…Arterial thrombus formation is the critical step in acute cardiovascular events such as myocardial infarction (Ross, 1999), and tissue factor (TF) is a key trigger of thrombus formation in vivo (Steffel et al, 2006). In addition, inflammation and in particular cytokines such as tumor necrosis factor alpha (TNF-α) (Yamamoto et al, 2002) have been proposed as potential mediators of stress related vascular events as have other components of the coagulation cascade as well as platelets (Larsson et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…More recent analyses estimate that more than 700,000 patients present with sepsis yearly in the United States resulting in 215,000 deaths of which the majority are elderly people [7, 8]. Although age-related dysregulation of the inflammatory response and thrombosis appear to be involved [9-11], the precise mechanisms for the age-dependent vulnerability to sepsis remain unclear.…”
Section: Introductionmentioning
confidence: 99%